The Conflict Between Good and Evil in the Harry Potter Series (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Introduction: The Harry Potter series by J. K. Rowling presents a complex and compelling portrayal of the eternal conflict between good and evil.Aim: This article aims to analyze how the opposition of good and evil is represented through characters, symbolism, and moral choices.Methods: The research applies descriptive, comparative, and interpretative literary analysis methods.Results: The analysis demonstrates that moral choice, rather than birth or magical ability, defines goodness and evilness in the series.Conclusion: Rowling emphasizes that ethical values such as love, loyalty, and responsibility serve as the strongest forces against darkness.The Harry Potter series by J. K. Rowling presents a complex and compelling portrayal of the eternal conflict between good and evil. This article examines how the author employs characters, symbolism, moral choices, and the magical world to represent the constant struggle between these opposing forces. Particular attention is given to major characters such as Harry Potter, Lord Voldemort, Albus Dumbledore, and Severus Snape, whose actions and decisions shape the moral framework of the narrative. The study concludes that Rowling emphasizes a key ethical message: good and evil are defined not by birth, blood, or talent, but by individual choices.